Understanding the money–prices relationship under low and high inflation regimes: Argentina 1977–2006 - Basco, Emiliano (2009)
We study the regime dependence of the money–prices relationship, focusing on Argentina's experience over the last 30 years. Using descriptive and cointegration analysis we find that proportionality holds for the high inflation period but weakens once inflation lowers. Money velocity correlates positively with money growth under high inflation, while this relation reverts under low inflation. VAR analysis allows to identify the key role of inflation expectations in driving the short-run dynamics of the money growth–inflation relationship under high inflation. Although this relationship weakens under low inflation, money continues to play a role in explaining inflation dynamics in Argentina.